Protein recovery, separation and purification: selection of optimal techniques using an expert system - Eduardo W. Leser; Juan A. Asenjo (Memorias do Instituto Oswaldo Cruz, 1994)
The paper discusses the utilization of new techniques ot select processes for protein recovery, separation and purification. It describesa rational approach that uses fundamental databases of proteins molecules to simplify the complex problem of choosing high resolution separation methods for multi component mixtures. It examines the role of modern computer techniques to help solving these questions.